Identifying the role of cloud computing technology in management of educational institutions. (2022) - Naved, Mohd; Sanchez, Domenic T.; Dela Cruz, Adeline P.; Peconcillo, Larry B.; Peteros, Emerson D.; Tenerife, Janine Joy L.
Abstract: Cloud computing refers to a computer architecture that offers universal on-demand network access to a shared pool of configurable resources. Educational institutions are essential because they play a vital role in policy formulation and contribute to cultural, political, and social growth. Cloud computing is highly popular throughout the IT sector worldwide, and its importance and excitement is also expanding in educational institutions' IT demands. There is currently little information available on the use of cloud computing in educational institutions. Organizations can use cloud computing to decrease IT costs while also gaining more flexibility and scalability; nevertheless, the sustainability of many cloud computing services remains to be seen. Measures to address security, privacy, and legal concerns, as well as the standardization of cloud technology, are still in the works. This article discusses the importance of cloud computing technologies in educational institution management. This also presents a number of problems in terms of cloud computing adoption in educational institutions.